SOSIALISASI PEMANFAATAN SAMPAH ORGANIK MENJADI PUPUK KOMPOS DAN POC - Samsuar, Samsuar; Alpi Yunita (Abdi Techno, 2022)
Currently, waste is one of the big problems faced by the Indonesian government, both in processing and reducing waste generation. As time goes by, the population in Indonesia has increased every year. Especially in Parombean village itself, with the increase in population, the amount of waste generated also increases. Therefore, we have to take care of our own environment. In this work program, it is a place to provide understanding to the community to protect our environment by processing waste generated from household activities, especially organic waste. One of the efforts to protect our environment is the utilization of organic waste, especially household waste, into compost and POC. The purpose of this activity is to increase the sense of community responsibility to protect the environment and also provide understanding to the community about how to make compost and POC from household waste. The Thematic Real Work Lecture for Wave 106 has been successfully carried out with the result of raising public awareness about the importance of keeping the environment clean and reusing organic waste into compost and POC.